PENERAPAN PENDEKATAN SAINTIFIK MATERI PERSAMAAN DAN PERTIDAKSAMAAN NILAI MUTLAK LINEAR SATU VARIABEL PADA SISWA SMK KELAS X - Luthfiani, Evi; Yuliani, Anik; Afrilianto, M. (IKIP Siliwangi, 2023)
This research is a classroom action research conducted with 2 cycles. This research was conducted on Merger class students X TKJ and TKRO of SMK Dwi Putra Sindangkerta for the academic year 2022/2023 using a scientific approach. This study aims to determine classroom action research and understanding of mathematical concepts, especially the material equations and inequalities of linear absolute value of one variable using a scientific approach. In this study, the results of students' answers using data analysis techniques with qualitative analysis have four stages: 1). Data collection; 2). Data reduction; 3). Data presentation; 4). Conclusion. The first cycle's lack of student activity was demonstrated by the average score of 62.70 for all students, Student scores increased by 24.58 from the average initial test score of 38.12. In the second cycle test the results have increased the average score of 38.12, student scores climbed by 24.58. It can be concluded that the mastery of the concept of linear absolute value equations and inequalities of one variable in Merger X TKJ and TKRO class students at Dwi Putra Sindangkerta Vocational School has increased.